Tc1 Cells Percentage in Patients with Cutaneous Leishmaniasis before and after Treatment with Glucantime - M Mohajery; AA Shamsian; M Mahmoodi (Tehran University of Medical Sciences, 2007)
Background: Various responses and different prognosis to specific treatment in different patients from one hand, and importance of IFN-γ producer cells on the other hand impressed us to study Tc1. Methods: The study was conducted in Ghaem Medical Center and Bu-Ali Research Institute, Mashhad University of Medical Sciences, Iran from 2001 to 2002. Lymphocytes of 36 patients were counted and cultured. Percentage of different responsible immunity cells in 29 patients, were determined by Flow Cytometry System before and after medication with glucantime (IM). Patients who showed improvement after the treatment were put into group 1 and those who did not recover were labeled group 2. In this self-control clinical trial, sampling method was consecutive non-probability and the results were analyzed by t-test consequently. Results: The percentage of Tc1 cells showed a significant increase despite of being stimulated with Phorpol-Mristate-Acetate (PMA) among the whole studied patients and group 1 (P= 0.069 and P= 0.040, respectively). While no significant change was observed among patients in group 2. Conclusion: This verifies the influence of Tc1 cells for the treatment of patients with CL and perhaps the role of glucantime in improving the cell immunity response through increasing such cells.